Ibn ‘Arabī, Fiqh, and a Literal Reading of the Qur’an: Approaching the Outward Divine Commands as a Spiritual Realization - Lien Iffah Naf'atu Fina (UIN Sunan Kalijaga Yogyakarta, 2018)
Ibn ‘Arabī is sometimes regarded as unorthodox, refusing the outward aspects of religion. In fact, Ibn ‘Arabī writes hundreds of pages on the topics of fiqh and is a serious proponent of Sharī’ah as the only way to gain the divine Truth or spiritual realization. He proposes to read the text literally (spiritual literalism). This paper discusses fiqh and an approach of reading Qur’anic commands from a spiritual perspective through his lens. Ibn ‘Arabī believes that each ḥukm has both its outer and inner or spiritual dimensions, which is uncovered through a literal reading. He criticizes the use of ra’y and qiyas as a method of legal reasoning. His spiritual approach results in a democratization of ijtihād and authority. While this paper discusses its application of this approach to verses on ‘ibādāt, as mainly conducted by Ibn ‘Arabī himself in the Futūḥāt, it also touches on how this approach be applied and useful in the modern context.[Ibn ‘Arabī terkadang dianggap menolak aspek luar agama. Kenyataannya, Ibn ‘Arabī menulis ratusan halaman tentang topik fikih dan berpandangan bahwa Sharī’ah adalah satu-satunya jalan menuju Kebenaran atau realisasi spiritual. Dia mengusulkan untuk membaca teks secara harfiah (literalisme spiritual). Tulisan ini membahas pemikiran fikih dan pendekatan yang ditawarkan Ibn ‘Arabī dalam memahami ayat-ayat Al-Qur'an dari perspektif sufistiknya. Ibn 'Arabī meyakini bahwa setiap “hukum” dalam al-Qur ’an memiliki dimensi luar dan dimensi dalam, yang ditemukan melalui pembacaan literal. Dia mengkritik penggunaan ra‘y dan qiyās sebagai metode penalaran hukum. Pendekatan spiritualnya menghasilkan demokratisasi ijtihad. Penerapan pendekatan Ibn ‘Arabī terhadap ayat-ayat tentang ‘ibādāt, seperti ditemukan di Futūḥāt, akan dibahas di tulisan ini. Selain itu, artikel ini akan mendiskusikan bagaimana pendekatan literalisme spiritual ini diterapkan dan bermanfaat untuk konteks modern.]